2011
DOI: 10.1039/c1cc11007a
|View full text |Cite
|
Sign up to set email alerts
|

Highly ordered acid functionalized SBA-15: a novel organocatalyst for the preparation of xanthenes

Abstract: Post-synthesis modification of SBA-15 has been carried out to design highly ordered acid functionalized hybrid mesoporous organosilica, AFS-1. This material has been used as an efficient heterogeneous organocatalyst for the syntheses of xanthenes under mild conditions in the absence of any other metal co-catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(66 citation statements)
references
References 29 publications
(11 reference statements)
1
65
0
Order By: Relevance
“…The development of new heterogeneous organocatalysts other than metal-based heterogeneous catalysts has attracted a lot of attention owing to their several advantages including the robustness, low toxicity without metal-leaching problem during the reactions, inertness to moisture and oxygen, and simple handling and storage capability in the vicinity of green chemistry [10,11]. Recently, a few successful studies have been reported regarding the incorporation of urea based HBD molecules onto the solid architectures to overcome abovementioned problems.…”
Section: Introductionmentioning
confidence: 99%
“…The development of new heterogeneous organocatalysts other than metal-based heterogeneous catalysts has attracted a lot of attention owing to their several advantages including the robustness, low toxicity without metal-leaching problem during the reactions, inertness to moisture and oxygen, and simple handling and storage capability in the vicinity of green chemistry [10,11]. Recently, a few successful studies have been reported regarding the incorporation of urea based HBD molecules onto the solid architectures to overcome abovementioned problems.…”
Section: Introductionmentioning
confidence: 99%
“…In one approach surface carboxylic acid ( CO 2 H) functionalized mesoporous silica has been prepared via Schiff-base condensation of 3-aminopropyl grafted SBA-15 [36]. In the other case sulfonic acid ( SO 3 H) functionalized mesoporous silica has been prepared from 3-mercaptopropyl grafted MCM-41 via partial oxidation with hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both the acid functionalized materials can be used as catalyst for the condensation reaction of aromatic aldehyde and 2-naphthol to prepare different value added xanthene derivatives. The CO 2 H functionalized mesoporous silica can be used as a catalyst under ambient conditions in the presence of dichloromethane (DCM) as the solvent, whereas for the SO 3 H functionalized material catalysis proceeds under solvent-free conditions at 363 K. Synthesis of CO 2 H functionalized mesoporous silica, AFS-1 has been carried out as described in our previous communication (Scheme 1) [36].…”
Section: Introductionmentioning
confidence: 99%
“…A literature search revealed that many procedures have been developed for the preparation of the biologically important xanthene derivatives, 14-aryl-14H--dibenzo[a,j]xanthenes, through the dehydration of β-naphthol and aromatic aldehydes in the presence of various catalysts, such as AcOH-H 2 SO 4 , 7 selectfluor (1-(chloromethyl-4-fluoro-1,4-diazoniabicyclo [2.2.2]octane bis(tetrafluoroborate)), 8 wet cyanuric chloride, 9 Sc[N(SO 2 C 8 F 17 ) 2 ] 3 in a fluorine-containing solvent, 10 17 and sulfonic acid-functionalized silica (SiO 2 -Pr-SO 3 H). 18 In the same manner, the synthesis of 1,8-dioxooctahydroxanthenes was achieved through the dehydration of dimedone (5,5-dimethylcyclohexane-1,3--dione) and aromatic aldehydes in pseudo three-component reactions in the presence of a catalyst, such as, tetrabutylammonium hydrogen sulfate, 19 Sc 3+ -montmorillonite, 20 HClO 4 -SiO 2 and polyphosphoric acid (PPA)-SiO 2 , 21 phosphomolybdic acid (PMA)-SiO 2 , 22 acidic ionic liquids, 23 heteropoly tungstic acid (HPWA) loaded Si-mobile crystalline material (HPWA-MCM-41) mesoporous molecular sieves, 24 silica-supported Preyssler nanoparticles (SPNP), 25 MCM--41-RSO 3 H, 26 acid functionalized SBA-15 and MCM-41, 27 and silica-bonded N-propylsulfamic acid (SBNPSA).…”
Section: Introductionmentioning
confidence: 99%